Asuhan Keperawatan Keluarga pada Tn. STerutama pada An. Yk dengan Masalah Gizi Kurangdi Desa Sanggung, Gatak, Sukoharjo - Lestiani, Ayun Fitria; , Supratman, Ph.D (2015)
Background: Malnutrition is a complex problem that occurred in Indonesia. Indonesian children are essentially born with a normal weight and length.The real growth failure would be basicallyseen by the age of four months to two years. According data from the World Health Organization ( WHO , 2008) malnutrition is one of the health problems that should receive serious attention . Children who experience the problem of malnutrition in the Sukoharjo as much as 10% Objective: To describe the family nursing care in malnutrition patients which include assessment, intervention, implementation, and nursing evaluation. Results: After nursing care for 3 days in 3 times of visitation: able to recognize the problem of malnutrition, take the right decisions, can make modisco and prepare nutritionally balanced menu, modify and utilize the health care environment. Conclusion: In providing family nursing care and clients with malnutrition, it is required an approach and more attention from all parties, especially family. As well as from local health workers to deal with health problems in fulfilling clients' nursing care so that malnutrition problems do not continuously occur. Keywords: malnutrition, kwashiorkor, marasmus, imbalance nutrition: less than body requirements, lack of knowledge.